Meningkatkan Maharah Kalam Siswa MTs Kelas VII Mambaus Sholihin Melalui Penggunaan Media Gambar - Farid Qomaruddin (Jurnal Pendidikan Bahasa Arab, 2024)
This study aims to improve the speaking skills of seventh-grade students at the Mamba’us Sholihin School through the implementation of the "Picture Viewing" strategy. The research employs a classroom action research methodology, structured in two cycles to assess the effectiveness of the intervention. The sample consists of seventh-grade students, with data collected through observations, interviews, and tests to evaluate their speaking abilities before and after the application of the new strategy. The findings indicate a significant enhancement in student performance following the implementation of the Picture Viewing strategy. In the first cycle, the results were unsatisfactory, with a majority of students struggling with their speaking skills. However, after applying the new strategy in the second cycle, there was a marked improvement, as evidenced by an increase in the number of students achieving grades of "A" and "B." The study recommends the adoption of innovative teaching strategies in the instruction of Arabic language skills, particularly speaking, to foster increased student engagement and motivation. It also suggests that teachers create a stimulating learning environment that encourages students to express their ideas confidently. In conclusion, the research underscores the importance of collaboration between teachers and students, utilizing educational methods that cater to their needs, ultimately leading to improved learning outcomes and enhanced communication skills. The continuous improvement in speaking proficiency relies on adapting to student requirements, facilitating their effective expression in the language.